Book reviews: Aram V. Arutyunov and Valeri Obukhovskii; Convex and set-valued analysis. Selected topics, De Gruyter Graduate, De Gruyter, Berlin 2017, viii+201 p., ISBN: 978-3-11- 046028-5/pbk; 978-3-11-046030-8/ebook. - PETRUȘEL, Adrian (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The book, consisting of two relatively independent parts, is based on courses taught by the first author at the Moscow State University and by the second one at the Voronezh University. A preliminary Russian version, written by the first author, was published in 2014 with Fizmatlit Editors, Moscow, but the present book contains many additions and extensions.